Pengaruh Kerjasama Tim dan Kompetensi Terhadap Kinerja perawat Rumah Sakit Permata Bunda Medan - Putri Handayani Siregar; Muhammad Yamin Siregar; Isnaniah LKS (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2020)
This study aims to find out and prove "The Effect of Teamwork and Competence on the Performance of Nurses at Permata Bunda Medan Hospital" This type of research is associative which is a question of the relationship between two variables. The data analysis technique uses multiple linear analysis with hypothesis testing using t test, f test and coefficient of determination. the results of the discussion and conclusions indicate that teamwork and competence partially and simultaneously have a positive and significant effect on the nurse's performance at Permata Bunda Medan Hospital.